A comparative study: Influence of various drying methods on essential oil components and biological properties of Stachys lavandulifolia. Issue 5 (8th March 2021) - Hazrati, Saeid; Lotfi, Kazem; Govahi, Mostafa; Ebadi, Mohammad‐Taghi
Abstract: The genus Stachys is a member of the Lamiaceae family. These are important medicinal plants which grow all over the world and are known for their flavoring and therapeutic effects and Stachys lavandulifolia is an endemic species of Iran. To acquire high‐quality essential oil (EO), drying technique was implemented which is an essential part of this process. The present study designed to evaluate the influences of different drying techniques (fresh sample, shade, sunlight, freeze‐drying, microwave, and oven‐drying (40, 60, and 80°C) on EO yield and composition of S. lavandulifolia . The results indicated that the maximum EO yield was obtained by the shade‐drying method. The main compounds found in the fresh samples were spathulenol, myrcene, β‐pinene, δ‐cadinene, and α‐muurolol, while spathulenol, cyrene, δ‐cadinene, p‐cymene, decane, α‐terpinene, β‐pinene, and intermedeol were found to be the dominant compounds in the dry samples. Drying techniques were found to have a significant impact on the values of the main compositions, for example, monoterpene hydrocarbons such as α‐pinene, β‐pinene, myrcene, and β‐phellandrene were significantly reduced by microwave drying, oven‐drying (40, 60, and 80°C), and sunlight‐drying methods. Drying techniques increased the antioxidant activity of S. lavandulifolia EOs especially those acquired by freeze‐drying with the half‐maximal inhibitory concentration (IC50 ) values 101.8 ± 0.8 mg/ml in DPPH assay and 315.2 ± 2.1 mg/ml in decreasing power assay. As a result, shade‐, sun‐, and oven‐drying (40°C) were found to be the most important techniques for attaining maximum yields of EO. Abstract : The present study designed to evaluate the influences of different drying techniques (fresh sample, shade‐drying, sunlight‐drying, freeze‐drying, and oven‐drying (40, 60, and 80°C), and microwave‐drying) on EO yield and composition of Stachys lavandulifolia .